Lessening the impact of poverty on children - Offord, David R (Pulsus Group Inc, 1999)
The present paper is divided into three sections. The first section deals with two issues: the impact of poverty on children and the hypothesized mechanisms by which poverty affects children. The second section discusses four guiding principles for programs that aim to reduce deficits in the quality of life and life chances of poor children. The third section describes promising intervention programs.